Proposal: An Efficient Security and Privacy Scheme based on Elliptic Curve Cryptography (ECC) for Vehicular Ad hoc Network (VANET) - Israa M. Al-dulaimi; Ayman Khalil (International Journal of Engineering and Management Research, 2020)
Vehicles in a vehicular ad-hoc network (VANET) broadcast information about the driving environment in the road. Due to the open-access environment, this means that the VANET is susceptible to security and privacy issues. However, none of the related works satisfies all security and privacy requirements. Besides, their proposed has huge overhead in terms of computation and communication. To address the above issues, we will propose the security and privacy scheme based on Elliptic Curve Cryptography (ECC) and one secure hash function. Hence the reliability of each message being signed and checked has been improved. The main aim of this work is to satisfy all aspect requirements of security and privacy and reduce the computational complexity of the system.